2008
DOI: 10.1507/endocrj.k08e-146
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Maturity-onset Isolated ACTH Deficiency (IAD) in 2005: Japanese Cohort Studies

Abstract: Abstract. The prevalence of isolated ACTH deficiency (IAD) in Japan remains to be determined. Both authors (T.Y. & K.K.) had unique opportunities to see all patients with maturity-onset IAD in particular areas. T.Y. regularly visited Tokunoshima Island in Kagoshima Prefecture (population of about 28,500) which has two acute-care hospitals. He has taken care of endocrine-metabolism cases in one hospital and kept in touch with an endocrine-oriented physician in another. K.K. has provided glucocorticoid supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 5 publications
0
9
1
Order By: Relevance
“…The resulting decline in production and secretion of ACTH causes chronic secondary adrenocortical insufficiency. Although considered an extremely rare disease, the number of diagnosed cases is increasing because knowledge of the disease and detailed endocrinology testing have become more widespread [3]. In particular, incidence is relatively high among men at 40-60 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting decline in production and secretion of ACTH causes chronic secondary adrenocortical insufficiency. Although considered an extremely rare disease, the number of diagnosed cases is increasing because knowledge of the disease and detailed endocrinology testing have become more widespread [3]. In particular, incidence is relatively high among men at 40-60 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Over 300 cases of IAD were reported between 1969 and 1994 in Japan, and an increasing number of cases have been reported since then 3. The prevalence of diagnosed cases is 1.91/1 000 000 in the Miyazaki prefecture, 7.3/1 000 000 in Tokushima area and 3.8/1 000 000 in Chuetsu district in Japan 5 6. There seems to be a substantial number of undiagnosed patients because clinical diagnosis is made when the patient becomes severely ill due to physical stress 7 8.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been believed that isolated ACTH deficiency is rare in old people, a recent study from Japan showed this is not necessarily true 5. The management of corticosteroid deficiency during exercise remains controversial partly because patients with adrenal insufficiency are heterogeneous, and it is difficult to perform statistical analyses between groups using any end point such as endurance and performance.…”
Section: Discussionmentioning
confidence: 99%